2021
DOI: 10.1364/oe.434656
|View full text |Cite
|
Sign up to set email alerts
|

Coherent X-ray beam expander based on a multilens interferometer

Abstract: A coherent X-ray beam expander based on a multilens interferometer is proposed in this paper. The multilens interferometer allows efficient generation of a highly diverging coherent beam up to several milliradians in the hard X-ray energy range. The optical properties of the interferometer were experimentally demonstrated at the ESRF ID13 undulator beamline (Grenoble, France), using 12.4 keV X-rays. The beam expander allowed us to control the angular size and photon flux density of the formed beam and enabled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…It should be noted that the use of a 100-lens interferometer as a beam expander makes it possible to control the angular size and photon flux density of the generated beam and is capable of operating both in coherent and incoherent modes 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the use of a 100-lens interferometer as a beam expander makes it possible to control the angular size and photon flux density of the generated beam and is capable of operating both in coherent and incoherent modes 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Planar refractive parabolic lenses with a physical aperture of 10 μm and 100-lens interferometers based on them were fabricated by using three different Si microfabrication technologies. The interferometer was developed and used as the Xray beam expander 7 .…”
Section: Introductionmentioning
confidence: 99%
“…One of the first nanofocusing PCRLs made of silicon (Snigirev et al, 2009) had the following parameters for the biconcave elements: aperture A = 50 mm, curvature radius R = A/8, minimum thickness d l = 2 mm, length of one element p l = d l + A 2 /4R. Later, PCRLs with apertures of 30 mm (Snigirev et al, 2014) and 10 mm (Zverev et al, 2021) were manufactured with the same ratios for the other parameters as indicated above.…”
Section: Computer Simulations and Their Analysismentioning
confidence: 99%
“…Typical examples of PCRLs made of silicon are presented in works by Snigirev et al (2009Snigirev et al ( , 2014 and Zverev et al (2021). They look like a sequence of elements in which each element is a biconcave lens, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%